Modified hierarchical 3D-torus network - Rahman, M.M. Hafizur; Inoguchi, Yasushi; Horiguchi, Susumu (2005)
Three-dimensional (3D) wafer stacked implementation (WSI) has been proposed as a promising technology for massively parallel computers. A hierarchical 3D-torus (H3DT) network, which is a 3D-torus network of multiple basic modules in which the basic modules are 3D-mesh networks, has been proposed for efficient 3D-WSI. However, the restricted use of physical links between basic modules in the higher level networks reduces the dynamic communication performance of this network. A torus network has better dynamic communication performance than a mesh network. Therefore, we have modified the H3DT network by replacing the 3D-mesh modules by 3D-tori, calling it a Modified H3DT (MH3DT) network. This paper addresses the architectural details of the MH3DT network and explores aspects such as degree, diameter, cost, average distance, arc connectivity, bisection width, and wiring complexity. We also present a deadlock-free routing algorithm for the MH3DT network using two virtual channels and evaluate the network's dynamic communication performance under the uniform traffic pattern, using the proposed routing algorithm. It is shown that the MH3DT network possesses several attractive features including small diameter, small cost, small average distance, better bisection width, and better dynamic communication performance.